Weimar on the Pacific : German exile culture in Los Angeles and the crisis of modernism - Bahr, Ehrhard (Weimar and now, 2007)
In the 1930s and '40s, LA became a cultural sanctuary for a distinguished group of German artists and intellectuals - including Thomas Mann, Theodor W. Adorno, Bertolt Brecht, Fritz Lang, and Arnold Schoenberg - who were fleeing Nazi Germany. This book is the first to examine their work and lives.